2019
DOI: 10.1002/jso.25727
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of a large mesenteric mass >2 cm in ileal neuroendocrine tumors

Abstract: Background and Objectives Ileal neuroendocrine tumors (i‐NETs) frequently metastasize to mesenteric lymph nodes and the liver. Regional lymphadenopathy is associated with desmoplasia of the mesentery forming a large mesenteric mass (LMM). Although the latest American Joint Committee on Cancer TNM staging (8th edition) defined LMM >2 cm as N2, the prognostic impact of LMM is ill‐defined. We evaluated whether LMM is prognostic for patients with i‐NETs. Methods This single‐institution, retrospective cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Only the MM contact ≥180° with SMV was independently associated with these symptoms. This finding is in line with the results of a previous study that showed that large MM (>2 cm) were as frequent among patients with a history of small bowel obstruction as smaller MM [21]. This could also be related to the small size of our study population.…”
Section: Discussion/conclusionsupporting
confidence: 93%
“…Only the MM contact ≥180° with SMV was independently associated with these symptoms. This finding is in line with the results of a previous study that showed that large MM (>2 cm) were as frequent among patients with a history of small bowel obstruction as smaller MM [21]. This could also be related to the small size of our study population.…”
Section: Discussion/conclusionsupporting
confidence: 93%
“…Reasons to opt for an open resection were related to better lymphadenectomy and tactile feedback. An adequate lymphadenectomy is of particular importance, as presence of lymph nodes have a negative impact on survival, irrespective of presence of liver metastases, and is complex in case of N2 nodes [8,13]. However, it should be noted that no differences between the number of resected lymph nodes were reported between minimally invasive and open resection by any of the comparative studies, and that R0 resection rates were higher in the minimally invasive group [3,7,9,10].…”
Section: Discussionmentioning
confidence: 91%
“…Regional lymphadenopathy was associated with desmoplasia and fibrosis of the mesentery forming a mesenteric mass, which may impact on clinical and staging features in SBNETs (42)(43)(44). The updated AJCC 8th edition had incorporated mesenteric masses in staging for midgut NETs, but the prognostic validity of this classification has yet to be validated.…”
Section: Discussionmentioning
confidence: 99%